Implementasi Good Corporate Governance Pada Perusahaan Sector Consumer Goods Industry dan Pengaruhnya Terhadap Tax Avoidance - Asy Syuaroh, Asy Syuaroh; Evana, Einde; Putri, Widya Rizki Eka (Sultan Journal of Social Sciences and Humanities, 2024)
This study aims to examine the effect of the good corporate governance on tax avoidance. This study focused on consumer goods industry companies listed on the Indonesia Stock Exchange in 20162020. This research is motivated by the phenomena about tax avoidance. Good corporate governance in this study uses proxy of the institutional ownership, independent board of commissioners, audit committee, and the audit quality as independent variables. The dependent variable is the tax avoidance measured using the cash effective tax rate (CETR) companies are paying taxes divided by income before income taxes. The sample in this study were 148 obtained from the purposive sampling method. The analysis technique used in this research is multiple linear regression analysis. From these results it can be seen that the audit committee has a significant negative effect on tax avoidance. Institutional ownership and the audit quality has no significant effect on tax avoidance, while the independent board of commisssioners has positive effect on tax avoidance